Pregnancy in a didelphic uterus: a case report of an unusual phenomenon and review of literature - Ekanem, Emmanuel; Lalrinawmi, Lalrinawmi; Sinha, Anita; Abdelrazik, Tamer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Mullerian anomalies are defects in the embryological development of the urogenital systems as these organs begin to form at about the 5 and 6th week of intrauterine life. Uterine didelphys is one of the Mullerian or paramesonephric duct anomalies occurring as a result of duplication of the uterine canal with two cervical canals and a single vagina. The incidence uterine didelphys has been quoted as 1 in 2000 women. This case report elucidates the presentation of a multiparous lady with uterine didelphys who had a previous successful pregnancy in of the uterine canals but presented in the second pregnancy with a missed miscarriage at 12 weeks gestational age. She also had a single right kidney. These were all diagnosed on ultrasound scan. She had an initial unsuccessful surgical management of miscarriage with uterine perforation of one of the uterine cavities diagnosed on hysteroscopy and diagnostic laparoscopy. She subsequently had examination under anaesthesia and an attempt at evacuation of retained products and a second look laparoscopy. This was particularly challenging as the cervix was flushed with the vaginal vault making delineation and dilatation of the cervical OS difficult hence sustaining a perforation at the left uterine cavity. The second attempt of surgical management was successful, and she was subsequently discharged. This is one of the few case reports in literature and will further add credence to the body of knowledge of a different aspect to the presentation and management of cases of Mullerian anomalies.